Correction: Hereditary gynecological cancer management in women with Lynch syndrome: a survey across Europe - Kevin J. J. Kwinten; Joanne A. de Hullu; Helen Bolton; Monique M. A. Brood-van Zanten; Valentina Chiappa; Stefan Cosyns; Sergi Fernandez-Gonzalez; Angelique Flöter Rådestad; Sophie Frank; Rieke Gellner; Susanne Housmans; Nina Kovacevic; et al. (Familial Cancer, 2026)

Hereditary gynecological cancer management in women with Lynch syndrome: a survey across Europe - Kevin J. J. Kwinten; Joanne A. de Hullu; Helen Bolton; Monique M. A. Brood-van Zanten; Valentina Chiappa; Stefan Cosyns; Sergi Fernandez-Gonzalez; Angelique Flöter Rådestad; Sophie Frank; Rieke Gellner; Susanna Housmans; Nina Kovacevic; et al. (Familial Cancer, 2026)
We aim to compare clinical practices in the gynecological management of women with Lynch syndrome across Europe and assess the need for multidisciplinary gynecological care for this high-risk population. European gynecologists involved in the clinical care of women with Lynch syndrome were invited to complete a cross-sectional survey regarding their clinical practices and organization of care. All participating gynecologists were based in hospitals that are members of the European Reference Network on Genetic Tumour Risk Syndromes (ERN GENTURIS). A total of 33 gynecologists (57%) from 25 unique hospitals across 12 countries participated in the survey. National guidelines on the gynecological management of women with Lynch syndrome were absent in a significant number of European countries. Local multidisciplinary team meetings were available in 61% of hospitals. Considerable heterogeneity was reported in the organization of care, as well as in surveillance, prevention, and treatment strategies. Standardized European guidelines for the gynecological care of women with Lynch syndrome are warranted to promote uniformity. Gynecologists specialized in hereditary cancer should take the lead in developing and implementing these guidelines. Hospitals managing women with Lynch syndrome should have the resources to organize multidisciplinary team meetings, which are crucial for the effective implementation of these guidelines and the improvement of personalized care.

Structural signatures of language reorganization after left hemispherotomy in patients with Rasmussen’s encephalitis - Anna Borne; Marcela Perrone-Bertolotti; Christine Bulteau; Emilie Cousin; Elise Roger; Monica Baciu (Brain Structure and Function, 2025)

Retraction Note: Verapamil Inhibits Ser202/Thr205 Phosphorylation of Tau by Blocking TXNIP/ROS/p38 MAPK Pathway - Mariarosa Anna. Beatrice Melone; Clemente Dato; Simona Paladino; Cinzia Coppola; Claudia Trebini; Maria Teresa Giordana; Lorena Perrone (Pharmaceutical Research, 2024)

Electrochemotherapy of skin metastases from malignant melanoma: a PRISMA-compliant systematic review - Martina Ferioli; Valentina Lancellotta; Anna Myriam Perrone; Alessandra Arcelli; Andrea Galuppi; Lidia Strigari; Milly Buwenge; Francesca De Terlizzi; Silvia Cammelli; Roberto Iezzi; Pierandrea De Iaco; Luca Tagliaferri; et al. (Clinical & Experimental Metastasis, 2022)
The main treatment of MM metastases are systemic therapies, surgery, limb perfusion, and intralesional talimogene laherparepvec. Electrochemotherapy (ECT) is potentially useful also due to the high response rates recorded in cancers of any histology. No randomized studies comparing ECT with other local therapies have been published on this topic. We analyzed the available evidence on efficacy and toxicity of ECT in this setting. PubMed, Scopus, and Cochrane databases were screened for paper about ECT on MM skin metastases. Data about tumor response, mainly in terms of overall response rate (ORR), toxicity (both for ECT alone and in combination with systemic treatments), local control (LC), and overall survival (OS) were collected. The methodological quality was assessed using a 20-item validated quality appraisal tool for case series. Overall, 18 studies were included in our analysis. In studies reporting “per patient” tumor response the pooled complete response (CR) was 35.7% (95%CI 26.0–46.0%), and the pooled ORR was 80.6% (95%CI 68.7–90.1%). Regarding “per lesion” response, the pooled CR was 53.5% (95%CI 42.1–64.7%) and the pooled ORR was 77.0% (95%CI 56.0–92.6%). One-year LC rate was 80%, and 1-year OS was 67–86.2%. Pain (24.2–92.0%) and erythema (16.6–42.0%) were the most frequent toxicities. Two studies reported 29.2% and 41.6% incidence of necrosis. ECT is effective in terms of tumor response and tolerated in patients with skin metastases from MM, albeit with a wide variability of reported results. Therefore, prospective trials in this setting are warranted.

Simultaneous monitoring of SARS-CoV-2 and bacterial profiles from the air of hospital environments with COVID-19-affected patients - Maria Rita Perrone; Salvatore Romano; Giuseppe De Maria; Paolo Tundo; Anna Rita Bruno; Luigi Tagliaferro; Michele Maffia; Mattia Fragola (Aerobiologia, 2022)
The SARS-CoV-2 presence and the bacterial community profile in air samples collected at the Intensive Care Unit (ICU) of the Operational Unit of Infectious Diseases of Santa Caterina Novella Hospital in Galatina (Lecce, Italy) have been evaluated in this study. Air samplings were performed in different rooms of the ICU ward with and without COVID-19 patients. No sample was found positive to SARS-CoV-2, according to Allplex 2019-nCoV Assay. The airborne bacterial community profiles determined by the 16S rRNA gene metabarcoding approach up to the species level were characterized by richness and biodiversity indices, Spearman correlation coefficients, and Principal Coordinate Analysis. Pathogenic and non-pathogenic bacterial species, also detected in outdoor air samples, were found in all collected indoor samples. Staphylococcus pettenkoferi, Corynebacterium tuberculostearicum , and others coagulase-negative staphylococci , detected at high relative abundances in all the patients’ rooms, were the most abundant pathogenic species. The highest mean relative abundance of S. pettenkoferi and C. tuberculostearicum suggested that they were likely the main pathogens of COVID-19 patients at the ICU ward of this study. The identification of nosocomial pathogens representing potential patients’ risks in ICU COVID-19 rooms and the still controversial airborne transmission of the SARS-CoV-2 are the main contributions of this study.

New insights on the occurrence and conservation status in Italy of Alessioporus ichnusanus (Boletaceae), an IUCN red listed mycorrhizal species - Paola Angelini; Daniele Antonini; Massimo Antonini; Andrea Arcangeli; Pietro Massimiliano Bianco; Giancarlo Bistocchi; Luca Campana; Andrea Ceci; Francesca Floccia; Maria Letizia Gargano; Matteo Gelardi; Giorgio Lalli; et al. (Plant Biosystems, 2021)

Values and challenges in the assessment of coprophilous fungi according to the IUCN Red List criteria: the case study of Poronia punctata (Xylariales, Ascomycota) - Andrea Ceci; Paola Angelini; Mirco Iotti; Giorgio Lalli; Marco Leonardi; Giovanni Pacioni; Luigi Perrone; Silvia Pioli; Carmine Siniscalco; Veronica Spinelli; Giuseppe Venturella; Robert P. Wagensommer; et al. (Plant Biosystems, 2021)

Electrochemotherapy of skin metastases from breast cancer: a systematic review - Martina Ferioli; Anna Myriam Perrone; Milly Buwenge; Alessandra Arcelli; Alice Zamagni; Gabriella Macchia; Francesco Deodato; Savino Cilla; Luca Tagliaferri; Francesca De Terlizzi; Pierandrea De Iaco; Claudio Zamagni; et al. (Clinical & Experimental Metastasis, 2021)

Revised Accelerated Moment Release Under Test: Fourteen Worldwide Real Case Studies in 2014–2018 and Simulations - Gianfranco Cianchini; Angelo De Santis; Rita Di Giovambattista; C. Abbattista; L. Amoruso; S. A. Campuzano; M. Carbone; C. Cesaroni; Anna De Santis; D. Marchetti; L. Perrone; A. Piscini; et al. (Pure and Applied Geophysics, 2020)

Early Behavioral Alterations and Increased Expression of Endogenous Retroviruses Are Inherited Across Generations in Mice Prenatally Exposed to Valproic Acid - Anna Maria Tartaglione; Chiara Cipriani; Flavia Chiarotti; Benedetta Perrone; Emanuela Balestrieri; Claudia Matteucci; Paola Sinibaldi-Vallebona; Gemma Calamandrei; Laura Ricceri (Molecular Neurobiology, 2019)

Methylation of cytokines gene promoters in IL-1β-treated human intestinal epithelial cells - Fabio Caradonna; Ilenia Cruciata; Ilaria Schifano; Chiara La Rosa; Flores Naselli; Roberto Chiarelli; Anna Perrone; Carla Gentile (Inflammation Research, 2018)

RETRACTED ARTICLE: Verapamil Inhibits Ser202/Thr205 Phosphorylation of Tau by Blocking TXNIP/ROS/p38 MAPK Pathway - Mariarosa Anna. Beatrice Melone; Clemente Dato; Simona Paladino; Cinzia Coppola; Claudia Trebini; Maria Teresa Giordana; Lorena Perrone (Pharmaceutical Research, 2018)

Molecular characterisation and pathogenicity of Aspergillus Sect. Nigri causing Aspergillus vine canker of table grapes in Italy - Alessandro Vitale; Gabriella Cirvilleri; Anna Panebianco; Filomena Epifani; Giancarlo Perrone; Giancarlo Polizzi (European Journal of Plant Pathology, 2012)

A case of haemorrhagic cystitis by inhaled salbutamol and salmeterol - Sonia Radice; Anna Milanesi; Stefania Antoniazzi; Valentina Perrone; Carla Carnovale; Emilio Clementi (European Journal of Clinical Pharmacology, 2011)

Phytotoxic polyketides produced by Phomopsis foeniculi, a strain isolated from diseased Bulgarian fennel - Antonio Evidente; Rossitza Rodeva; Anna Andolfi; Zornitsa Stoyanova; Carmen Perrone; Andrea Motta (European Journal of Plant Pathology, 2011)

Coronary computerized tomography angiography for rapid discharge of low-risk patients with cocaine-associated chest pain - Kristy M. Walsh; Anna Marie Chang; Jeanmarie Perrone; Christine M. McCusker; Frances S. Shofer; Mark J. Collin; Harold I. Litt; Judd E. Hollander (Journal of Medical Toxicology, 2009)